2021
DOI: 10.1002/cti2.1358
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein flare‐response predicts long‐term efficacy to first‐line anti‐PD‐1‐based combination therapy in metastatic renal cell carcinoma

Abstract: Objectives Immune checkpoint blockade (IO) has revolutionised the treatment of metastatic renal cell carcinoma (mRCC). Early C‐reactive protein (CRP) kinetics, especially the recently introduced CRP flare‐response phenomenon, has shown promising results to predict IO efficacy in mRCC, but has only been studied in second line or later. Here, we aimed to validate the predictive value of early CRP kinetics for 1st‐line treatment of mRCC with αPD‐1 plus either αCTLA‐4 (IO+IO) or tyrosine kinase inhibitor (IO+TKI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Recently, for the first-line treatment of metastatic RCC, we have shown that early CRP kinetics predicts response and is associated with improved PFS also for the immunotherapy combinations, anti-PD-1 either plus anti-CTLA-4 or tyrosine kinase inhibitor, suggesting that early CRP kinetics seems to be relevant not only for anti-PD-1 monotherapy. 7 Further, within the framework of the prospective validation cohort, we were able to closely examine early CRP kinetics through the standardized study visits. Our data demonstrate that CRP kinetics can stratify patients as early as 4 weeks after the onset of ICB, a significant period before the first radiological assessment which is usually performed at week 8-12.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, for the first-line treatment of metastatic RCC, we have shown that early CRP kinetics predicts response and is associated with improved PFS also for the immunotherapy combinations, anti-PD-1 either plus anti-CTLA-4 or tyrosine kinase inhibitor, suggesting that early CRP kinetics seems to be relevant not only for anti-PD-1 monotherapy. 7 Further, within the framework of the prospective validation cohort, we were able to closely examine early CRP kinetics through the standardized study visits. Our data demonstrate that CRP kinetics can stratify patients as early as 4 weeks after the onset of ICB, a significant period before the first radiological assessment which is usually performed at week 8-12.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fukuda et al described a novel on-treatment CRP kinetics in metastatic renal cell carcinoma, which is associated with significant tumour shrinkage and improved outcome in metastatic renal cancer patients treated with nivolumab monotherapy [12]. We demonstrated early CRP kinetics to be associated with improved response to first-line anti-PD-1-based combination therapies in mRCC [17]. In a small retrospective cohort of only 31 patients with mUC, early CRP kinetics was associated with response to immunotherapy, but CRP flare kinetics were observed in only three patients (<10%) [18].…”
Section: Introductionmentioning
confidence: 65%
“…In particular, high CRP levels before ICI treatment are associated with poor treatment response and prognosis (18)(19)(20)(21)(22)(33)(34)(35) ; conversely, elevated CRP levels within 1 week after ICI initiation predict good treatment e cacy and prognosis (23) . Furthermore, recent reports have shown that a CRP are response, de ned as a transient increase in serum CRP levels after ICI initiation followed by a subsequent decrease below baseline, is associated with better prognosis in renal cell carcinoma, urothelial carcinoma, and lung cancer (24,31,(36)(37)(38) . However, the de nition was calculated with CRP kinetics within 12 weeks after ICI initiation, which is slower than the rst imaging to examine clinical e cacy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CRP, age, PS, LDH, NLR, and albumin have been reported to correlate with the treatment e cacy and prognosis of ICI treatment (20,31,33,34,37,45,46) . The present study showed that CRP-increase is associated with higher PS, LDH, and NLR and lower haemoglobin and albumin in the gastric cancer cohort, and higher NLR and lower haemoglobin and albumin in the oesophageal cancer cohort.…”
Section: Discussionmentioning
confidence: 99%